IT Instruments Used in the Omnichannel Retail Strategy to Fulfil General Data Protection Regulation Requirements - Norbert ZYCZYNSKI; Wieslaw LEWICKI (Communications of International Proceedings, 2021)
The European Union introduced its data protection standard already over 25 years ago with the introduction of Directive 95/46/EC regarding the protection of individuals with respect to the processing of personal data and the free movement of such data which gave Member States flexibility in implementing it into national law, which resulted in many inconsistent legal systems relating to data protection. In addition, the last years have brought an increase in the number of security violations and rapid technological developments which combined with the globalisation process, have brought new challenges in the area of personal data protection. Due to their decentralised structure, retail organisations, which are often active in many countries and which focus on omnichannel strategy, have to adapt their procedures to the new legal environment. The lack of implementation of the rights required by General Data Protection Regulation (GDPR) may lead to serious financial and reputational consequences. In addition, the omnichannel strategy which by definition implies transparent integration of all distribution channels, looks particularly difficult in the context of personal data protection.
Keywords: GDPR; protection of personal data; prevention and monitoring of data violations; retail management; omnichannel strategy.